Blood fury [compact disc, unabridged] : Black Dagger legacy - Ward, J. R., 1969- (Ward, J. R., 1969- Black dagger legacy., 2018)
A tough vampire warrior in training and her fellow aristocratic trainee struggle to deny the attraction they feel for one another as they prepare for the looming war ahead.